2000
DOI: 10.2224/sbp.2000.28.3.293
|View full text |Cite
|
Sign up to set email alerts
|

Learning to Work Safely With Reference to a Social-Cognitive Model

Abstract: Issues concerning the effectiveness of promotional activities for working people's occupational safety and health are the focus of the present study. Data were collected from a random sample of 668 working people in Hong Kong by the telephone survey method. The study relies on a framework of social cognitive theory, which posits mediational roles of beliefs concerning one's self-efficacy, the collective efficacy of the promotional organization, and the efficacy of behavior for occupational safety and health. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Many studies have shown that intentions account for a considerable proportion of variance in behavior (Hrubes et al, 2001;Sheeran, 2002). Other studies that found a relationship between intention and behaviors include Armitage and Conner (2001), Notani (1998); Randall and Wolff (1994), Sheppard et al (1988); Cheung and Chan (2000), Rivis and Sheeran (2003); Schulze and Wittmann (2003). Since actual behaviors are usually difficult to measure, it is quite common to measure the behavioral intention as a surrogate to some actual behaviors (Zhang et al, 2014).…”
Section: Theory Of Reasoned Actionmentioning
confidence: 99%
“…Many studies have shown that intentions account for a considerable proportion of variance in behavior (Hrubes et al, 2001;Sheeran, 2002). Other studies that found a relationship between intention and behaviors include Armitage and Conner (2001), Notani (1998); Randall and Wolff (1994), Sheppard et al (1988); Cheung and Chan (2000), Rivis and Sheeran (2003); Schulze and Wittmann (2003). Since actual behaviors are usually difficult to measure, it is quite common to measure the behavioral intention as a surrogate to some actual behaviors (Zhang et al, 2014).…”
Section: Theory Of Reasoned Actionmentioning
confidence: 99%
“…Few studies on agriculture have identified associations between farming practices, attitudes, and other psychological determinants [ 13 , 20 ]. Furthermore, the theory of planned behavior, an extension of the theory of reasoned action, has been extensively applied and tested in various fields [ 21 ]. The theory of planned behavior identifies hierarchical relations between various beliefs and attitudes affecting behavior.…”
Section: Introductionmentioning
confidence: 99%
“…In social behavior studies, the theory of planned behavior (TBP) has been extensively applied and tested in various fields, since it is an extension of the theory of reasoned action (Cheung & Chan, 2000;Sneed & Morisky, 1998). Furthermore, TBP can be used to identify hierarchical relationships among various beliefs and attitudes in regard to behavior.…”
mentioning
confidence: 99%